EFFECTIVE SPECTRUM SHARING METHOD USING POWER ALLOCATION ALGORITHM IN COGNITIVE RADIO NETWORKS - E.D.Kanmani Ruby; S. Nithya; N. Saranya (European Scientific Journal, ESJ, 2014)
Major problem in cognitive radio network is frequent handoff between the spectrum bands which is sensed to be idle for the usage of the secondary users. Whenever the spectrum is utilized by the primary users the secondary user has to be looking for the free idle band in order to avoid the interference between the licensed and unlicensed user because of which the handoff between the secondary have been increasing between the idle spectrum bands. To avoid the frequent handoff and the efficient usage of spectrum of bands we propose a new power allocation algorithm. This algorithm not only adjusts the transmission power of the secondary user but also provides interference constraint between the primary and secondary user, through which the secondary user can obtain more spectrum for the usage. Finally the simulation result of the power allocation algorithm is illustrated and demonstration of the proposed scheme is shown.